Group Investigation Method: Intervensi Pengembangan Kecerdasan Interpersonal Peserta Didik - Bambang Setiawan (Prophetic : Professional, Empathy, Islamic Counseling Journal, 2024)
This study aims to examine the effectiveness of group counseling services using the group investigation method in developing students' interpersonal intelligence. Interpersonal intelligence is crucial for students' social success but is often neglected in its development. This research employed a quantitative approach with a quasi-experimental method, comparing two groups (experimental and control) using a nonequivalent pretest-posttest control group design. The experimental group received treatment in the form of group counseling using the group investigation method, while the control group received no treatment. The instrument used to measure interpersonal intelligence was validated and tested for reliability, with 78 out of 87 items deemed valid and a reliability score of 0.922. Data analysis was conducted using independent t-tests, normality tests, and homogeneity of variance tests. The results showed a significant difference between the average post-test scores of interpersonal intelligence in the experimental group compared to the control group. Additionally, the gain analysis indicated a significant increase in the experimental group, demonstrating the effectiveness of the group investigation method in developing interpersonal intelligence. In conclusion, group counseling services with the group investigation method are effective in enhancing students' interpersonal intelligence, as evidenced by the significant increase in interpersonal intelligence scores in the experimental group. These findings underscore the importance of targeted nurturing and learning to develop students' interpersonal intelligence.